MANUAL DE CONTROL INTERNO PARA LA EMPRESA “DIMACO” DE LA CIUDAD DE LOJA - Sarmiento Sucunuta, Yessenia Fernanda (2019)
The present work of investigation denominated "MANUAL OF INTERNAL CONTROL FOR THE COMPANY" DIMACO "OF THE CITY OF LOJA", is directed to promote an appropriate handling of the resources and to determine the correct operation of the company with the purpose of looking for the effectiveness, efficiency and economics of business management. Likewise, this thesis work has been proposed and developed under the guidelines of the National University of Loja, as a prerequisite to opt for the degree of Accounting and Audit Engineer, Auditor CPA Auditor. The completion of the Internal Control Manual allowed to reach the objectives set at the beginning of the project; For the situational diagnosis, one of the research techniques was applied, such as interviewing all the company's personnel, thus evidencing deficiencies in the procedures, lack of policies and lack of an internal control manual, which prevented the optimal decision making in the company. Likewise, after a thorough review of regulations, laws and regulations issued by the regulatory bodies, policies and procedures were established in order to safeguard resources and achieve business goals and objectives, for which a manual of procedures was prepared in the which details the policies, objectives and procedures for each activity carried out by the company and in turn establishes a manual of functions aimed at the staff of the entity where they describe the 5 responsibilities they have according to their job, in order to avoid duplication of functions and finally, the flowcharts were designed for the activities of creation, use and replacement of the petty cash fund, cash settlement, bank reconciliations, acquisition and sale of merchandise, physical verification of inventories, payment to suppliers, declaration of taxes, hiring and training of personnel, registration of contracts with the Ministry of Labor, payment of remunerations, application for vacation leave and preparation of final settlement records; facilitating its understanding through the use of flowcharts, a technique that details in a logical and sequential manner the process to follow, in order to promote the quality and speed of operations to achieve the objectives of the same. Therefore, the conclusions and recommendations of the results obtained are presented, highlighting the importance of the Manual of Internal Control in the company "DIMACO" and its application, therefore it will allow the owner to have an adequate control of its resources and that the operations be carried out efficiently and effectively in order to ensure the reasonableness and reliability of your information.